A Vehicle-in-the-Loop (VIL) verification of an all-autonomous intersection control scheme. (October 2019) - Fayazi, S. Alireza; Vahidi, Ardalan; Luckow, Andre
Highlights: A traffic management scheme is proposed for an all-autonomous intersections. The vehicle scheduling problem is reduced to a mixed-integer linear program (MILP). A detailed implementation of a vehicle-in-the-loop verification environment is presented. A method to estimate the fuel rate by basic On-Board Diagnostics data is proposed. The MILP-controlled intersection resulted in about 20% benefit in fuel consumption. Abstract: In this paper, an implementation of a vehicle-in-the-loop (VIL) verification environment is presented tailored to automated intersection traffic management applications. Although the fundamental goal of this implementation is to evaluate our proposed optimal traffic management scheme for autonomous vehicles, the test environment is configurable and reproducible to incorporate most of the real time intersection control methods for verification purposes. In our cyber-physical virtual testing environment, actual test vehicles and intersection control server at the physical layer interact with simulated vehicles in an implemented traffic microsimulation layer. The intersection control server continuously runs a Mixed Integer Linear Program (MILP) that was previously proposed by authors for vehicle arrival scheduling at all-autonomous intersections with no physical traffic lights. In addition to the novel intersection traffic management scheme at the cyber layer, this VIL environment also includes a fuel consumption tracker that is based on our proposed fuel rate estimation methods using the basic vehicle diagnostic data. Using this environment, the mobility efficacy and the fuel consumption reduction potential of the proposed intersection control scheme are compared with two baseline scenarios in VIL experiments.